2017
DOI: 10.1002/hbm.23765
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term language switching training tunes the neural correlates of cognitive control in bilingual language production

Abstract: The present study investigated how language switching experience would modulate the neural correlates of cognitive control involved in bilingual language production. A group of unbalanced Chinese-English bilinguals undertook an 8-day cued picture naming training during which they named pictures in either of their languages based on visually presented cues. Participants' brain activation was scanned before and after the training in the same task. Behavioral results revealed a significant training effect such th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 65 publications
1
30
0
Order By: Relevance
“…Neurobiological investigations using these paradigms have additionally found that language switching as prompted by a cue elicits engagement of executive control regions, mainly the prefrontal cortex [7][8][9][17][18][19], the pre-supplementary motor area/anterior cingulate cortex (pre-SMA/ ACC) [7,8,[19][20][21][22][23][24], and the left caudate nucleus [23][24][25][26][27] (see meta-analysis in [18] and reviews in [26][27][28][29][30]). The literature stemming from this paradigm has proven highly consistent, with widely replicated results across the world in multilingual individuals with many different linguistic backgrounds [7][8][9][10][11][12][13][14][15][16][17][20][21][22][23][24][25]. As a result, this work has formed the main empirical basis for models of bilingual language switching.…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…Neurobiological investigations using these paradigms have additionally found that language switching as prompted by a cue elicits engagement of executive control regions, mainly the prefrontal cortex [7][8][9][17][18][19], the pre-supplementary motor area/anterior cingulate cortex (pre-SMA/ ACC) [7,8,[19][20][21][22][23][24], and the left caudate nucleus [23][24][25][26][27] (see meta-analysis in [18] and reviews in [26][27][28][29][30]). The literature stemming from this paradigm has proven highly consistent, with widely replicated results across the world in multilingual individuals with many different linguistic backgrounds [7][8][9][10][11][12][13][14][15][16][17][20][21][22][23][24][25]. As a result, this work has formed the main empirical basis for models of bilingual language switching.…”
mentioning
confidence: 70%
“…According to this hypothesis, bilingual individuals, as a mere consequence of being bilingual develop an improved cognitive control system. Because the neural underpinnings of language control and general domain executive control overlap to some extent [8][9][10]25,[64][65][66][67]; cf. [11,68], this enhancement in language control mechanisms is proposed to generalize to nonlinguistic tasks, resulting in an advantage in many tasks requiring selective attention and inhibition (for comprehensive reviews see [69][70][71][72]).…”
Section: Experience Dependent Bilingual Advantagementioning
confidence: 99%
See 3 more Smart Citations